ANALISIS EFISIENSI TEKNIS DALAM PENINGKATAN PRODUKSI WORTEL DI DESA SUMBER BRANTAS KECAMATAN BUMIAJI KOTA BATU - dina kartika sari (Program Studi Agribisnis, 2019)
ABSTRACTThe increase in carrots in Indonesia is fluctuating and tends to decrease so that to fulfill their consumption needs to be done through imports, therefore a study of increasing carrot production needs to be done.This research is to knowing the analysis of the technical efficiency of production factors in increasing carrot production in Sumber Brantas Village.With a population of farmers as many as 144 people and using a slovin method that obtained 60 samples that adequately represented the population. The results of analysis using Cobb-Douglass; Stochastic Frontier for technical efficiency gets production factors that have partial effects, namely land, labor, sigma squared, gamma on ineficiency socio-economic factors that is age, family members, experience, activation in farmer groups (Dummy) with level different significanceKeyword : carrot, eficiency